Preservation and storage of butterfly DNA using filter paper - GÓMEZ-P., LUZ MIRYAM; URIBE, SANDRA I. (Revista Colombiana de Entomología, 2007)
Two techniques for butterfly DNA storage were compared using Polymerase Chain Reaction (PCR) amplification of a fragment from the ND4 gene. Extracted DNA was put into microcentrifuge tubes and stored at -20°C; alternatively, they were put on filter paper and stored at ambient temperatures. Fragments of DNA amplified through PCR that came from filter paper exhibited high quality. Our results suggest storage on filter paper to be a simple, effective and inexpensive alternative to preserve extracted DNA.